Ritual Capital for Rural Livelihood and Sustainable Tourism Development in Indonesia - Yerik Afrianto Singgalen; Gatot Sasongko; Pamerdi Giri Wiloso (Jurnal Manajemen Hutan Tropika, 2019)
Sustainable livelihood approach has been a strategic approach that can improve the economy of rural communities and create harmonization of socio-cultural, economic, environmental and political development through policies. However, it is holistic and contextual, enabling the existence of different capital characteristics formed based on the community's culture. The Indonesian context shows that customary rituals of the community in Kakara and Limau villages in North Halmahera Regency are forms of capital that mobilize claims and access to capital such as natural, human, physical, financial, and social capital. This article aims to describe the ritual capital in rural livelihood for sustainable tourism development. Key informants involved were leaders of community, traditions, religion and rural government and they were interviewed to obtain in-depth information about the ritual capital. The results indicate that the ritual capital was integrated with the rural tourism development, enhancing the capabilities of the customary community in the Kakara and Limau Village to access other capital. This finding supports the argument explaining that ritual capital is a livelihood asset in the context of tourism development in North Halmahera Regency, Indonesia.